2015
DOI: 10.1152/jn.00319.2015
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal stimulus timing-dependent plasticity in primary auditory cortex is altered after noise exposure with and without tinnitus

Abstract: Basura GJ, Koehler SD, Shore SE. Bimodal stimulus timingdependent plasticity in primary auditory cortex is altered after noise exposure with and without tinnitus. J Neurophysiol 114: 3064 -3075, 2015. First published August 19, 2015 doi:10.1152/jn.00319.2015.-Central auditory circuits are influenced by the somatosensory system, a relationship that may underlie tinnitus generation. In the guinea pig dorsal cochlear nucleus (DCN), pairing spinal trigeminal nucleus (Sp5) stimulation with tones at specific interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 59 publications
8
44
0
Order By: Relevance
“…These findings cohere with animal studies of Basura et al (), Ralli et al (), Shore et al (), and Turner et al (), which showed that a gap (stimulus intensity decrease) may be useful in studying lab‐induced tinnitus; it was proposed that the internally generated sound perceived by the animals would fill a silent gap and diminish or remove inhibition that would have been caused by the gap, resulting in larger magnitude startle responses, compared to those of control animals. The results from the current study can explain the findings to a further degree: If tinnitus constitutes an inability to hear silence, and hence fills a gap, less inhibition would be expected on decrease trials than on increase trials, but partial inhibition of startle magnitude would still be expected.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings cohere with animal studies of Basura et al (), Ralli et al (), Shore et al (), and Turner et al (), which showed that a gap (stimulus intensity decrease) may be useful in studying lab‐induced tinnitus; it was proposed that the internally generated sound perceived by the animals would fill a silent gap and diminish or remove inhibition that would have been caused by the gap, resulting in larger magnitude startle responses, compared to those of control animals. The results from the current study can explain the findings to a further degree: If tinnitus constitutes an inability to hear silence, and hence fills a gap, less inhibition would be expected on decrease trials than on increase trials, but partial inhibition of startle magnitude would still be expected.…”
Section: Discussionsupporting
confidence: 89%
“…Animals can be conditioned to respond to the termination of noise, and the inability to detect the cessation of noise after salicylate exposure is a model of tinnitus (Jastreboff & Sasaki, 1994;Ruttiger, Ciuffani, Zenner, & Knipper, 2003). Across a variety of studies, the induced tinnitus-like animals have been shown to demonstrate less inhibition of startle magnitude on fully silent gap trials, compared to control animals (Basura, Koehler, & Shore, 2015;Ralli et al, 2014;Shore, Roberts, & Langguth, 2016;Turner, Larson, Hughes, Moechars, & Shore, 2012). These findings suggest that the tinnitus-associated sound perception partially fills the silent gap, reducing the expected inhibition of startle responding.…”
Section: Introductionmentioning
confidence: 99%
“…Burst firing increased immediately after noise trauma but subsided to normal over the measurement period of a few hours while the changes in SFR and synchrony persisted. While tinnitus was not measured in these experiments, subsequent studies confirmed that there was increased cortical synchrony and SFR in animals with verified tinnitus, using the GPIAS, giving credence to the validity of hyperactivity and synchrony as neural correlates of tinnitus [72]. …”
Section: Neurophysiological Alterations In Animal Models Of Tinnitusmentioning
confidence: 91%
“…If one believes that increased SFR in the auditory nervous system, and particularly in ACx, is a neural correlate of tinnitus (Eggermont and Roberts, 2004; Roberts et al, 2010; Basura et al, 2015), then a few additional noise-exposure effects demand attention. After a single TTS-causing exposure—which constitutes the bulk of current animal experiments involving gap-startle indications of tinnitus—one often finds increased SFRs and the gap-startle reflex indicates (Salloum et al, 2014, 2016) the presence of tinnitus.…”
Section: Tinnitus Networkmentioning
confidence: 99%
“…An overview of some of these findings, augmented with results from Basura et al (2015) and Wu et al (2016) that are likely TTS causing, is presented in Table 4 . Again, assuming that increased SFRs in ACx suggest the presence of tinnitus, one has to come to the conclusion that tinnitus cannot only occur in humans with clinical normal thresholds (≤25 dB HL) but also with absolute normal thresholds (Gu et al, 2010; Melcher et al, 2013).…”
Section: Tinnitus Networkmentioning
confidence: 99%